2005
DOI: 10.1213/01.ane.0000140781.18391.41
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Propofol and Sevoflurane on the QT Interval and Transmural Dispersion of Repolarization in Children

Abstract: Prolongation of the QT interval is associated with torsades de pointes (TdP), especially in children or young adults with long QT syndromes. Susceptibility to TdP arises from increased transmural dispersion of repolarization (TDR) across the myocardial wall. Several anesthetic drugs prolong the QT interval, but their effect on TDR is unknown. TDR can be measured on the electrocardiograph (ECG) as the time interval between the peak and end of the T wave (Tp-e). We investigated the effects of propofol and sevofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 40 publications
5
76
1
1
Order By: Relevance
“…However, the increased QTc interval was within normal limit and no patients in this study had an arrhythmia. These findings are inconsistent with those from previous studies, which reported that propofol has no effect on the QT interval [8][9][10][11]. Our results also contradict Paventi et al [12], and Kleinsasser et al [13], who hypothesised that propofol may shorten the QTc interval.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, the increased QTc interval was within normal limit and no patients in this study had an arrhythmia. These findings are inconsistent with those from previous studies, which reported that propofol has no effect on the QT interval [8][9][10][11]. Our results also contradict Paventi et al [12], and Kleinsasser et al [13], who hypothesised that propofol may shorten the QTc interval.…”
Section: Discussioncontrasting
confidence: 99%
“…Slowly activating (iKs) and rapidly activating (iKr) delayed rectifier channels conduct most of the repolarisation current [21]. It is widely known that inhaled anaesthetic agents block iKr channels, and therefore increase the QTc interval in healthy patients [1,2,7,9,10]. There are no reports that have clearly investigated intravenous anaesthetics, including propofol's contribution to QTc prolongation, but according to Heath et al [22], propofol has been reported to block the delayed rectifier potassium current.…”
Section: ó 2008 the Authorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In both groups, sevoflurane lengthened the QTc and QTVI intervals but not Tp-e. Sevoflurane is a popular inhalational agent for general anaesthesia. It blocks the slowly activating delayed rectifier K current (I Ks ) and prolongs the QT interval in both children [1,2] and adults [3,4]. Such changes may be of clinical significance in patients presenting with long QT syndrome, hypokalaemia or in the presence of other agents or factors that lengthen the QT interval.…”
mentioning
confidence: 99%